Penerapan Anggaran Penjualan dalam Memperkirakan Penjualan - Victorianta Br Tarigan; Nurhayati Nurhayati (Journal of Business and Economics Research (JBE), 2022)
This study aims to estimate the income that will be obtained for the months of June to December 2022 at the Panglong Tarclo Jaya business and to determine the preparation of the sales budget so that the sales level is in accordance with the sales demand desired by consumers. Data collection techniques used in this study are: observation, interviews, and literature study. Technical analysis of data in forecasting sales is the method of trend moment and least square. After the sales forecast results are found, the company makes a Forecasting Standard Error (SKF) to compare between the two methods which method is the most appropriate to use. To compare the two methods, the Standard Error Forecast (SKF) is used. The results of the research through the SKF that have been carried out show the trend moment method with an SKF value of 78.04, and the least square method with an SKF value of 77.8. The better method to use is the least square method because the difference in the SKF value is 0.24 smaller. So the company uses the least square method in forecasting the sales budget. The sales budget for bricks in Panglong Tarclo Jaya from July 2022 to December 2022 is Rp. 399,277,500 with total sales of 798,600 pieces.